On one class of nonlinear operator equations in Hilbert spaces - Britov, N.A. (Нелинейные граничные задачи, 2000)
One special class of nonlinear operator equations depended from two real numerical parameters in Hilbert spaces are considered. Non-local conditions of existence and uniqueness of solutions are established. The conditions of admissibility of of solutions of linearized equation for description of solutions of considered equation are established.